1992
DOI: 10.1002/jbm.820261105
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal changes in compliance following implantation of bioresorbable vascular grafts

Abstract: Compliance matching between the host vessel and vascular grafts used for small-diameter arterial replacements is thought to be important for long-term patency. However, currently available grafts elicit fibroplastic reactions, resulting in decreasing compliance with time after implantation. Bioresorbable prostheses elicit ingrowth of myofibroblasts containing abundant contractile elements. This led us to investigate whether compliance of implanted bioresorbable prostheses decreased as a function of time and if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…The interaction of bacterial cellulose with vascular cells, such as that demonstrated here for SMCs, may even suggest adaptive remodeling of bacterial cellulose grafts in vivo and hence better compliance matching with host arteries in the long term. This is supported by the work of Greisler et al 28 where cellular ingrowth was found to increase the compliance of woven polyglactin 910 grafts implanted into rabbits. In addition, in the work by Roy et al, 29 decellularization of porcine carotid arteries was found to significantly reduce arterial compliance.…”
Section: Discussionsupporting
confidence: 52%
“…The interaction of bacterial cellulose with vascular cells, such as that demonstrated here for SMCs, may even suggest adaptive remodeling of bacterial cellulose grafts in vivo and hence better compliance matching with host arteries in the long term. This is supported by the work of Greisler et al 28 where cellular ingrowth was found to increase the compliance of woven polyglactin 910 grafts implanted into rabbits. In addition, in the work by Roy et al, 29 decellularization of porcine carotid arteries was found to significantly reduce arterial compliance.…”
Section: Discussionsupporting
confidence: 52%
“…Not surprisingly, pro-angiogenic growth factors were added to natural ingrowth matrices like fibrin (Greisler et al, 1992a) soon after their potential was discovered in vitro (Montesano et al, 1986). Alternatively, bioresorbable scaffolds were used for vascular grafts as soon as the potential of host tissue to regenerate structures became fully comprehended (Greisler et al, 1992b). The central role that macrophages play in this concept certainly contributed to a less "engineerable" outcome.…”
Section: Spontaneously Endothelializing Arterial Graftsmentioning
confidence: 99%
“…In addition to their use in classic applications, such as bioabsorbable sutures 1,2 and drug delivery systems, 3,4 their applicability recently expanded into new areas, such as selectively biodegradable vascular grafts, [5][6][7] noninvasive surgical procedures, 8,9 the prevention of postsurgical adhesions, [10][11][12] and tissue engineering. [13][14][15] Poly(-caprolactone) (PCL) is being used in clinics as a surgical material, and some of the most commonly reported PCL biomedical applications are controlled drug delivery systems 16 and implants for orthopedic surgery.…”
Section: Introductionmentioning
confidence: 99%